Kolmogorov widths of the classes $B^{Ω}_{p, θ}$ of periodic functions of many variables in the space $L_q$ - Solich, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain exact-order estimates for the Kolmogorov widths of the classes $B^{Ω}_{p, θ}$ of periodic functions of many variables inthe space $L_q$ for $1 ≤ p, q ≤ ∞$.